POLA KOMUNIKASI ANTARBUDAYA MAHASISWA ASAL THAILAND DI IAIN PALANGKA RAYA (Thailand Original Culture Communication Patterns In IAIN Palangka Raya) - Ngalimun Ngalimun (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2020)
The subjects of this study were all Thai students studying at IAIN Palangka Raya, totaling 9 people. While the object of this research is the pattern of intercultural communication of Thai students at IAIN Palangka Raya. Intercultural communication patterns Thai students in interacting with their environment can be seen from the interactions that occur in the communication process of each party. From the recognition of Thai students, the first beginning to arrive at IAIN Palangka Raya felt the cultural difficulties of Central Kalimantan, especially in the language that made it a shame to introduce themselves. But both students and lecturers and employees of IAIN Palangka Raya with a friendly and friendly nature can make Taufik and friends feel comfortable. Gradually Thai students can adapt to Indonesian so they are not ashamed to greet or make friends with Local students of IAIN Palangka Raya.